2016
DOI: 10.1002/wnan.1419
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular imaging of quantum dots, gold, and iron oxide nanoparticles with associated endocytic pathways

Abstract: Metallic nanoparticles (NP) have been used for biomedical applications especially for imaging. Compared to nonmetallic NP, metallic NP provide high contrast images because of their optical light scattering, magnetic resonance, X-ray absorption, or other physicochemical properties. In this review, a series of in vitro imaging techniques for metallic NP will be introduced, meanwhile their strengths and weaknesses will be discussed. By utilizing these imaging methods, the cellular uptake of metallic NP can be eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 129 publications
(250 reference statements)
0
12
0
Order By: Relevance
“…1 Similar to metallic quantum dots, CDs can also emit multicolour bright uorescence by adjusting the particle size. 4,5 However, CDs show signicant advantages due to their water dispensability, chemical inertness, good photostability, low cytotoxicity, and excellent biocompatibility compared with organic dyes and other semiconductor nanodots with heavy metal elements. The above-mentioned capabilities of CDs endow them a wide range of technology applications in gene/ drug delivery, 6,7 bio-imaging, 8 photocatalysis, 9 bio-sensing, 10 optoelectronic devices, 11 energy conversion/storage devices 12 and other bio-applications.…”
Section: Introductionmentioning
confidence: 99%
“…1 Similar to metallic quantum dots, CDs can also emit multicolour bright uorescence by adjusting the particle size. 4,5 However, CDs show signicant advantages due to their water dispensability, chemical inertness, good photostability, low cytotoxicity, and excellent biocompatibility compared with organic dyes and other semiconductor nanodots with heavy metal elements. The above-mentioned capabilities of CDs endow them a wide range of technology applications in gene/ drug delivery, 6,7 bio-imaging, 8 photocatalysis, 9 bio-sensing, 10 optoelectronic devices, 11 energy conversion/storage devices 12 and other bio-applications.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed a 14% increase in diameter of SPION NIRF-Rh dispersed in the culture medium (SFEM) used in the cells' labeling, in addition to showing another peak probably that corresponded to some of the proteins present in SFEM, with a hydrodynamic diameter of 9.3 nm. According to a study by Sousa de Almeida [30] in this condition is possible to affirm that the physical chemistry characteristics of SPION NIRF-Rh are favorable to the process of internalization into cells [30,31], as well as the probable endocytic pathway of internalization [30][31][32][33]. However, when this same condition of SPION NIRF-Rh +SFEM was supplemented with 10% FBS it was possible to observe little variability.…”
Section: Discussionmentioning
confidence: 79%
“…Compared to other metallic nanoparticles, gold nanoclusters are stable under the electron beam and provide excellent contrast in TEM. Thus, TEM is considered the best method to observe individual gold nanoparticles inside the cellular compartments [ 47 ].…”
Section: Resultsmentioning
confidence: 99%